Social media political information use and political participation of the net generation - Jue, Jun Tan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Given the pervasiveness of social media in our contemporary communication environment, this paper explored the aptitude of social media use for political information in empowering the wired youth with more diverse political information which is deemed as key precursor of political participation. To be more specific, this paper examined how the utilisation of political information on social media predicts political knowledge, political efficacy, and different modes of political participation (offline, online, and cyber) of the Net Generation. There were 379 Malaysian students aged between 18 and 24, who depend extensively on social media platforms as their primary reservoir of political news and information took part in a self-administered online survey questionnaire. Among the key findings of the current study are: (i) political informational use of social media predicts political efficacy but not political knowledge; (ii) political informational use of social media predicts offline, online, and cyber political participation via political efficacy; (iii) political knowledge does not predict political participation; meanwhile (iv) political efficacy predicts political participation. All in all, political informational use of social media holds the most potent positive effect on political efficacy.